SISTEM INFORMASI PELAYANAN PASANG BARU PADA PDAM TIRTA MUARO JAMBI BERBASISIS WEBSITE: Application, Informasi, Internet, PDAM, Sistem, Website, - Riswan, Riswan; Nilawati, Nilawati; Fikri, Al (FORTECH (Journal of Information Technology), 2025)
PDAM (Regional Drinking Water Company) of Mauro Jambi Regency is a government-owned enterprise engaged in the distribution of clean water. The problem faced by the PDAM of Mauro Jambi Regency is the difficulty of new installations and the appeal from the PDAM, and this has an impact on the less than optimal service for new installations. The solution offered is the creation of a new installation service system at PDAM Mauro Jambi Regency. The purpose of this research is to make it easier for admins to process data and make it easier for the community to install new ones. The method used is the method of analysis carried out by literature study of data collection (observation) and the method of software development using the waterfall method. The input from this research is admin data, new install customer data, appeals consist of admin data processing, new installation data processing, new installation data processing, and producing output in the form of new install customer reports, appeal reports. This research resulted in a new installation service information system at PDAM Muaro Jambi Regency to facilitate the community in installing PDAMs. so that customers do not have to come to the PDAM office, simply by accessing the PDAM Muaro Jambi Regency website.